The Geometry of the Universe: in Search of Unity. New Possible Mathematical Connections with the DN Constant, Ramanujan's Recurring Numbers and Some Parameters of Number Theory and String Theory (London Journal of Research In Science: Natural and Formal, 2025)
In this work, we analyze the DN Constant (Del Gaudio-Nardelli Constant). We will describe the possible mathematical connections with Ramanujan's Recurring Numbers, some parameters of Number Theory and String Theory
Keywords: Aleurodicusrugioperculatus; Aspergillus spp.; host crops and symbiosis; GIS; territorial planning; spatial sampling; urban growth